Neuroleptic Malignant Syndrome with Very High Serum Creatine Phosphokinase: A Case Report (BIRDEM Medical Journal, 2012)
The neuroleptic malignant syndrome (NMS), characterized by muscular rigidity, altered level of consciousness, dysautonomias and an elevated creatinine phosphokinase level, is a potentially lethal consequence of treatment with neuroleptics. Although it occurs most frequently with conventional anti psychotics, it may also occur with newer anti psychotic agents. Physicians need to have a high index of suspicion with regard to diagnosing NMS in patients taking neuroleptics regardless of duration or dose and presenting with hyperthermia. It is under diagnosed in critical care settings though various neuroleptics are frequently used in intensive care units for various purpose. We report a case involving a 55-yr old man with psychiatric disorder who presented with NMS with extremely elevated serum creatine phosphokinase level and acute renal failure. DOI: http://dx.doi.org/10.3329/birdem.v2i1.12363 Birdem Med J 2012; 2(1) 56-59